Can AI Personalize Healthcare Professional Training? - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2023)
The rapid advancements in artificial intelligence (AI) are transforming various sectors, and healthcare is no exception. From diagnostics to treatment plans,...
Keywords: AI in Medical Education and Future of Healthcare; Personalize; Healthcare; Professional; Artificial Intelligence; Diagnostics; Patient Care